Peru - Klepeis, Alicia, 1971- (2019)
"Engaging images accompany information about Peru. The combination of high-interest subject matter and narrative text is intended for students in grades 3 through 8"--
Includes bibliographical references (page 31) and index.
Ages 7-13
Keywords: Peru -- Juvenile literature